Apoptosis and Cancer: Mutations Relationship within Caspase 2 Genes in Turk Male Patients - İŞLER, Orcun and TURAÇLAR, Nesrin and VURAL, Hasibe Cingilli (International Journal of Medical Research and Review, 2015)
Introduction: Prostate cancer is the most frequently diagnosed male cancer in developed countries. Prostate cancer is the most common cancer diagnosed among men in Turkey, accounting for 42.5% of all cancer cases in men. It ranks second after lung cancer as the underlying cause of cancer death in Turk men. If cancer is a disease where too little apoptosis occurs there are other diseases where too much apoptosis is thought to be part of the problem. Caspases and apoptotic process very important role in modern cancer treatment. Material & Methods: For this reason, we study and analyzed 2 exons of the human caspase 2 gene, using a strategy combining RT-PCR amplification and HRM, followed in the second study, considered to investigate the associations between prostate cancer and caspase 2 gene expression and nucleotide sequence analysis in 12 individulas with prostate cancer and healthy persons. Result: As a result of working, variant-1 and variant-2 of caspase-2 gene mutation was identified in the tissues of the prostate using HRM method. For variant-1, 4 number one mutation was detected in the samples, while for variant-2, 2 numbered examples of mutation has been identified. Conclusion: According to the statistical evaluation in our study, there was significant difference in CSP2 mutations. At the same time, it has been evaluated with one-to-one correspondence tests whether presence of CSP2 mutation has relationship with the development of any clinical symptoms while diagnostic criteria.